In vivo biological behavior of calcium phosphate cements with different Ca/P ratio - Saska, S. [UNESP]; Nunes, N. S. [UNESP]; Aveiro, E. [UNESP]; Pavan, C. A C [UNESP]; Santagneli, S. H. [UNESP]; Campos, J. A D B [UNESP]; Gaspar, A. M M [UNESP]; Ribeiro, Sidney José Lima [UNESP]; Messaddeq, Younes [UNESP] (Trans Tech Publications, 2009)
Bioceramics with different Ca/P ratio were prepared from a mechanical mixture of NaPO3, CaCO3, Ca(OH)2 and phosphate buffer solution and implanted in rats subcutaneous tissues. The cements were characterized by Thermo gravimetric analysis (TG-TDA), X-ray diffraction and 31P-NMR. The implant sites were excised after 1, 4 and 16 weeks, fixed, dehydrated, included in paraffin wax for serial cutting and examined under the light transmitted microscope. They were biocompatible and biodegradable when implanted in rat subcutaneous. None of the materials induced ectopic osteogenesis. According to the results, the studied materials seem to be able for manufacturing reabsorbable bone implants.
Keywords: Biocompatibility; Calcium phosphate; In vivo test; Biological behaviors; Bone implants; Ca/p ratios; Calcium phosphate cements; Ectopic osteogenesis; In-vivo; Mechanical mixtures; Paraffin wax; Phosphate buffer solutions; Subcutaneous tissues; X- ray diffractions; Bioceramics; Bone cement; Calcium; Calcium alloys; Cements; Gravimetric analysis; Light; Paraffin waxes; Paraffins; Phosphates; Thermogravimetric analysis; X ray diffraction analysis